2021
DOI: 10.22226/2410-3535-2021-2-218-222
|View full text |Cite
|
Sign up to set email alerts
|

Unusual kinetics of strain-induced diffusional phase transformations in Cu-Cr-Zr alloy

Abstract: This paper reports experimental results demonstrating nonmonotonic changes of the solid solution concentration in the process of high-pressure torsion of the preliminary aged Cu-Cr-Zr alloy. The solid solution concentration which is very low in the initial state passes through a maximum before it finally stabilizes at a lower value. Such a behavior is, strictly speaking, impossible for a purely diffusion-controlled process under stationary conditions. Observations on the evolution of the second phases particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…The lattice parameter analysis by X-ray diffraction (XRD) showed that during ECAP processing, the lattice parameter was restored insignificantly (Table 2). The results are in the domain of statistical error, but based on the previous studies of alloys of this class [1,19,21,22], it can be suggested that there is a process of deformation-stimulated decay of the supersaturated SS. The Cu-0.2Cr and Cu-1.1Cr alloys showed almost the same level of lattice restoration during ECAP processing (~0.0006 Å).…”
Section: Research Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…The lattice parameter analysis by X-ray diffraction (XRD) showed that during ECAP processing, the lattice parameter was restored insignificantly (Table 2). The results are in the domain of statistical error, but based on the previous studies of alloys of this class [1,19,21,22], it can be suggested that there is a process of deformation-stimulated decay of the supersaturated SS. The Cu-0.2Cr and Cu-1.1Cr alloys showed almost the same level of lattice restoration during ECAP processing (~0.0006 Å).…”
Section: Research Resultsmentioning
confidence: 85%
“…The particles thus identified by X-ray analysis are chromium. The specimens were subjected to aging at a temperature of 450 • C [10,19,21,22], which is more characteristic for this class of alloys. Aging up to one hour was completed with an increment of 30 min, and further aging up to 5 h was performed with an increment of 1 h. Micro-hardness and electrical conductivity were measured at each increment.…”
Section: Aging Kinetics Of the Cu-02cr And Cu-11cr Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…Particles of the second phases can also promote corrosion development [ 12 ]. It is known that SPD methods can promote dynamic aging when the volume fraction of second-phase precipitates increases [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%